Spermatogenic cells of the prepuberal mouse: isolation and morphological characterization - Bellve, AR (The Rockefeller University Press, 1977)
A procedure is described which permits the isolation from the prepuberal mouse testis of highly purified populations of primitive type A spermatogonia, type A spermatogonia, type B spermatogonia, preleptotene primary spermatocytes, leptotene and zygotene primary spermatocytes, pachytene primary spermatocytes and Sertoli cells. The successful isolation of these prepuberal cell types was accomplished by: (a) defining distinctive morphological characteristics of the cells, (b) determining the temporal appearance of spermatogenic cells during prepuberal development, (c) isolating purified seminiferous cords, after dissociation of the testis with collagenase, (d) separating the trypsin-dispersed seminiferous cells by sedimentation velocity at unit gravity, and (e) assessing the identity and purity of the isolated cell types by microscopy. The seminiferous epithelium from day 6 animals contains only primitive type A spermatogonia and Sertoli cells. Type A and type B spermatogonia are present by day 8. At day 10, meiotic prophase is initiated, with the germ cells reaching the early and late pachytene stages by 14 and 18, respectively. Secondary spermatocytes and haploid spermatids appear throughout this developmental period. The purity and optimum day for the recovery of specific cell types are as follows: day 6, Sertoli cells (purity>99 percent) and primitive type A spermatogonia (90 percent); day 8, type A spermatogonia (91 percent) and type B spermatogonia (76 percent); day 18, preleptotene spermatocytes (93 percent), leptotene/zygotene spermatocytes (52 percent), and pachytene spermatocytes (89 percent), leptotene/zygotene spermatocytes (52 percent), and pachytene spermatocytes (89 percent).